Liraglutide Activates Type 2 Deiodinase and Enhances β3-Adrenergic-Induced Thermogenesis in Mouse Adipose Tissue - Oliveira, Fernanda C. B.; Bauer, Eduarda J.; Ribeiro, Carolina M.; Pereira, Sidney A.; Beserra, Bruna T. S.; Wajner, Simone M.; Maia, Ana L.; Neves, Francisco A. R.; Coelho, Michella S.; Amato, Angelica A. (Frontiers in Endocrinology, 2022)
Aims: Liraglutide is a long-acting glucagon-like peptide 1 (GLP-1) receptor agonist used as an anti-hyperglycemic agent in type 2 diabetes treatment and recently approved for obesity management. Weight loss is attributed to appetite suppression, but therapy may also increase energy expenditure. To further investigate the effect of GLP-1 signaling in thermogenic fat, we assessed adipose tissue oxygen consumption and type 2 deiodinase (D2) activity in mice treated with liraglutide, both basally and after β3-adrenergic stimulation. Methods: Male C57BL/6J mice were randomly assigned to receive liraglutide (400 g/kg, n=12) or vehicle (n=12). After 16 days, mice in each group were co-treated with the selective β3-adrenergic agonist CL316,243 (1 mg/kg, n=6) or vehicle (n=6) for 5 days. Adipose tissue depots were assessed for gene and protein expression, oxygen consumption, and D2 activity. Results: Liraglutide increased interscapular brown adipose tissue (iBAT) oxygen consumption and enhanced β3-adrenergic-induced oxygen consumption in iBAT and inguinal white adipose tissue (ingWAT). These effects were accompanied by upregulation of UCP-1 protein levels in iBAT, and UCP-1 mRNA and protein levels in ingWAT. Notably, liraglutide increased D2 activity without significantly upregulating its mRNA levels in iBAT, and exhibited additive effects to β3-adrenergic stimulation in inducing D2 activity in ingWAT. Conclusions: Liraglutide exhibits additive effects to those of β3-adrenergic stimulation in thermogenic fat and increases D2 activity in BAT, implying that it may activate this adipose tissue depot by increasing intracellular thyroid activation, adding to the currently known mechanisms of GLP-1A-induced weight loss.